Skills and Competencies Incompatible With Crime: A Theory of Criminal Lifestyle Change - Walters, Glenn D. (The prison journal, 2025)
This article presents a theory-based model of criminal desistance organized around the four behavioral styles of a criminal lifestyle. These four behavioral styles (irresponsibility, self-indulgence, interpersonal intrusiveness, and social rule breaking) were enlisted for the purpose of identifying four skill sets (accountability, introspection, empathy, and assimilation) with the power to serve as obstacles, deterrents, or barriers to continued criminal activity. Definitions, assessment procedures, intervention strategies, and changes in a person's involvements, commitments, and identifications are outlined for each skill set or competency, all in an effort to demonstrate the purpose, scope, and long-term value of each component of the model.